2012
DOI: 10.4236/wja.2012.24045
|View full text |Cite
|
Sign up to set email alerts
|

The Detrimental Effect of Adversity on HIV Outcomes in the Era of Combined Anti-Retroviral Therapy

Abstract: Socially disadvantaged individuals with HIV experience unacceptably high rates of AIDS and death. The authors developed an adversity index to quantify the impact of demographic and psychosocial factors on HIV care. This retrospective cohort study included 431 participants with HIV on combined antiretroviral therapy between 2000 and 2005. Poor outcome was defined as progression to AIDS, death, virologic failure, or CD4 < 200 cells/µl at six months. The index utilized eight demographic and psychosocial variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This was found almost similar to a recently published study which reported that side effects due to medications, lack of disease, and treatment knowledge as well as negative perceptions toward treatment were among the key elements to poor adherence (32), whereas perceived and experienced side effects, stigma, and status disclosure were reported barriers to adherence as reported by Mutwa et al (33). In fact side effects of antiretrovirals experienced by PLWHA are one of the most dominating clue to poor adherence explored by many studies around the world (32,34 38).…”
Section: Discussionmentioning
confidence: 99%
“…This was found almost similar to a recently published study which reported that side effects due to medications, lack of disease, and treatment knowledge as well as negative perceptions toward treatment were among the key elements to poor adherence (32), whereas perceived and experienced side effects, stigma, and status disclosure were reported barriers to adherence as reported by Mutwa et al (33). In fact side effects of antiretrovirals experienced by PLWHA are one of the most dominating clue to poor adherence explored by many studies around the world (32,34 38).…”
Section: Discussionmentioning
confidence: 99%
“…This study identified correlations that have been established in other samples, with MDE being correlated with alcohol abuse and dependence and GAD. [17][18][19] Providing comprehensive care to persons living with HIV, including addressing psychiatric and substance use disorders, is a significant challenge that requires the expertise of a multidisciplinary team approach. High rates of substance use disorders are likely to interrupt consistent engagement in care, 19 and thus addressing these disorders are a primary area of intervention.…”
Section: Discussionmentioning
confidence: 99%